Review detection of Newcastle disease virus - Mao, Qian; Ma, Shengming; Schrickel, Philip Luke; Zhao, Pengwei; Wang, Jingya; Zhang, Yuhua; Li, Shuangyu; Wang, Chengbao (Frontiers in Veterinary Science, 2022)
Newcastle disease (ND) is an acute and highly contagious disease caused by the Newcastle disease virus (NDV) infecting poultry, which has caused great harm to the poultry industry around the world. Rapid diagnosis of NDV is important to early treatment and institution of control measures. In this review, we comprehensively summarize the most recent research into NDV, including historical overview, molecular structure, and infection mechanism. We then focus on detection strategies for NDV, including virus isolation, serological assays (such as hemagglutination and hemagglutination-inhibition tests, enzyme linked immunosorbent assay, reporter virus neutralization test, Immunofluorescence assay, and Immune colloidal gold technique), molecular assays (such as reverse transcription polymerase chain reaction, real-time quantitative PCR, and loop-mediated isothermal amplification) and other assays. The performance of the different serological and molecular biology assays currently available was also analyzed. To conclude, we examine the limitations of currently available strategies for the detection of NDV to lay the groundwork for new detection assays.